Antioxidative action of methanolic extract and buthanolic fraction of Vochysia tucanorum Mart. in the gastroprotection - Gomes, Renata de Camargo [UNESP]; Bonamin, Flavia [UNESP]; Darin, Denise Delabio [UNESP]; Seito, Leonardo Noboru [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Dokkedal, Anne Ligia [UNESP]; Vilegas, Wagner [UNESP]; Monteiro Souza Brito, Alba Regina; Hiruma-Lima, Clélia Akiko [UNESP] (Elsevier B.V., 2009)
Aim of the study: Vochysia tucanorum is an important medicinal plant used in the Cerrado of Brazil against gastric disorders and this study reveals the pharmacological action of this traditional medicine use.Materials and methods: The methanolic extract (E-MeOH) and buthanolic fraction (Fr-Bu) obtained from V. tucanorum were challenged by different necrotizing agents in rodents. NO-synthase inhibitor (L-NAME) and SH blocker (NEM) were used to evaluate the participation of cytoprotective factors in E-MeOH and Fr-Bu gastroprotection. Antiulcerogenic action of V. tucanorum was evaluated in rats and mice at doses 250, 500 or 1000 mg/kg (E-MeOH) and 37.5, 75 or 150 mg/kg (Fr-Bu).Results: Both E-MeOH and Fr-Bu present elevated gastroprotective action in all in vivo experimental models, without signs of acute toxicity. The mechanisms involved in the gastroprotective action of E-MeOH and Fr-Bu are related to the antioxidant activity and protection to gastric mucosa NO levels. Phytochemical investigations of Fr-Bu identified different pentacyclic triterpenoids such as betulinic acid, erythrodiol, epi-betulinic acid and mixtures of ursolic acid and oleanolic acid derivatives as the major constituents. The presence of such triterpenoids in Fr-Bu is probably related to the potent gastro protective action of this medicinal plant species.Conclusion: Effectiveness in gastro protection and the absence of acute toxicity indicate this species as a promising herbal drug that is in accordance with ethnopharmacological use against gastric disorders. Published by Elsevier B.V.
Keywords: Vochysia tucanorum; Vochysiaceae; Gastric ulcer; Triterpenoids